2021
DOI: 10.1111/dom.14232
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of once‐weekly semaglutide versus once‐daily sitagliptin as add‐on to metformin in patients with type 2 diabetes in SUSTAIN China: A 30‐week, double‐blind, phase 3a, randomized trial

Abstract: Aim To evaluate the efficacy and safety of once‐weekly subcutaneous semaglutide, a glucagon‐like peptide‐1 (GLP‐1) analogue, versus once‐daily sitagliptin as add‐on to metformin in patients with type 2 diabetes (T2D) in a multiregional clinical trial. Materials and Methods In the 30‐week, randomized, double‐blind, double‐dummy, active comparator SUSTAIN China trial, 868 adults with T2D inadequately controlled on metformin (HbA1c 7.0%‐10.5%) were randomized to receive once‐weekly semaglutide 0.5 mg (n = 288), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 37 publications
2
65
0
6
Order By: Relevance
“…Both the subcutaneous and oral formulations of semaglutide have undergone extensive phase 3 clinical testing ( Table 1 ). For the once-weekly subcutaneous formulation, the SUSTAIN program (Semaglutide Unabated Sustainability in Treatment of Type 2 Diabetes) included 13 separate randomized clinical phase 3a and 3b trials ( 10 13 , 22 , 25 32 ) SUSTAIN 1 through 10 were global international trials, while three additional trials were specific for China and Japan. In four studies, semaglutide was compared with placebo, with differing patient populations.…”
Section: Semaglutidementioning
confidence: 99%
“…Both the subcutaneous and oral formulations of semaglutide have undergone extensive phase 3 clinical testing ( Table 1 ). For the once-weekly subcutaneous formulation, the SUSTAIN program (Semaglutide Unabated Sustainability in Treatment of Type 2 Diabetes) included 13 separate randomized clinical phase 3a and 3b trials ( 10 13 , 22 , 25 32 ) SUSTAIN 1 through 10 were global international trials, while three additional trials were specific for China and Japan. In four studies, semaglutide was compared with placebo, with differing patient populations.…”
Section: Semaglutidementioning
confidence: 99%
“…Among the included studies on subcutaneous semaglutide administration, five trials investigated its efficacy and safety compared to placebo (Marso et al, 2016;Sorli et al, 2017;Rodbard et al, 2018;Zinman et al, 2019b;Davies et al, 2021); nine trials assessed its efficacy and safety versus other antidiabetic drugs, including sitagliptin (Ahrén et al, 2017;Seino et al, 2018;Ji et al, 2020), canagliflozin (Lingvay et al, 2019), dulaglutide (Pratley et al, 2018), liraglutide (Capehorn et al, 2020), exenatide extended-release (Ahmann et al, 2018), insulin glargine (Aroda et al, 2017), and oral antihyperglycemic medications (Kaku et al, 2018). The sample size of these trials ranged from 302 in the SUSTAIN 9 study (Zinman et al, 2019b) to 3,297 in the SUSTAIN 6 study (Marso et al, 2016).…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…The participants in these trials were aged between 18 to 70 years old. Among all included studies, ten trials reported changes in BMI and weight [28,29,[35][36][37][38][39][40][41][42], two studies only reported BMI [43,44], and six studies only reported body weight [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%